The mediterranean policy of the EC—The case of agriculture - Stefan A. Musto (Intereconomics, 1983)
The production structures of the majority of Mediterranean countries have traditionally been oriented towards the West European market. What effects will the southward enlargement of the EC have on the agricultural sector of the non-candidate Mediterranean countries? What can the EC do to alleviate the problems?
Keywords: 330; Ec Enlargement